Pengaruh Perbedaan Laba Akuntansi dan Laba Fiskal, Tingkat Hutang, dan Ukuran Perusahaan Terhadap Pertumbuhan Laba (Studi Empiris Perusahaan Manufaktur yang Terdaftar di BEI Periode 2021-2024) - Salsa Novia Kusuma Putri; Dian Essa Nugrahini (Journal of Innovative and Creativity, 2025)
The study purpose was to explore the effects of variations in accounting profit, fiscal profit, company size, and debtlevels on profit growth among manufacturing firms listed on the Indonesia Stock Exchange (IDX) during the 2021–2024 period. This research aimed to provide empirical evidence on how internal financial performance indicators andcorporate structural factors interact to influence profitability within Indonesia’s manufacturing sector.Materials and methods. The study employed a quantitative research design using a causal framework. Secondaryfinancial data were collected from official company reports and IDX publications. A purposive sampling technique wasapplied to select 28 representative manufacturing companies that consistently published audited financial statementsthroughout the study period. Data analysis was conducted using multiple linear regression with SPSS version 26 toassess both partial and simultaneous effects of accounting–fiscal profit differences, debt levels, and firm size on profitgrowth.Results. The regression analysis showed that variations in accounting profit compared to fiscal profit and company size hadno significant effect on profit growth. However, the debt level had a positive and significant influence, indicating that firmswith higher leverage tended to experience increased profit growth. Simultaneous testing revealed that the three variablescollectively had a significant impact on profit growth, suggesting that the interaction between profitability measures andfinancial structure is crucial in determining firm performance.Conclusions. The study concludes that debt plays a key role in enhancing profit growth in Indonesian manufacturingfirms, while differences in accounting–fiscal profit recognition and company size contribute less significantly. It isrecommended that firms optimize their debt management strategies while maintaining accurate profit reportingstandardsto achieve sustainable financial growth and competitivenessin the industrial sector.